Glycerol in the diet of ruminant animals: advantages of its use - Delgado, A.; Galindo, Juana L. (Cuban Journal of Agricultural Science, 2024)
<header> This study delves into some topics related to the use of glycerol in ruminant feeding. The main ways to obtain glycerol are discussed and its properties are characterized. Its energetic value is highlighted due to the importance of its inclusion in diets for animals. Some studies are analyzed in which the use of glycerol in dairy and beef cattle was evaluated, as well as its effect on intake and productive indicators. In addition, general aspects related to metabolism are emphasized and the limitations related to its use are exposed. It is concluded that glycerol, which is obtained as a by-product in the manufacture of biofuels, can be included as an energy concentrate in diets intended for ruminants, as long as its methanol level is considered. </header>